Low impact development stormwater techniques: lessons learned from Topeka, Kansas, case studies - Young, Jacob A. (Kansas State University, 2006)
Low Impact Development (LID) is an emerging ecological method for planning and designing stormwater management. The main goal of LID is that post development hydrology mimic predevelopment hydrology or that of the natural land pattern. The difference between LID and conventional end of pipe engineering is that LID is designed for on-site infiltration. LID was developed in Maryland and has since been adapted to other ecoregions. The introduction and background offer a review of the importance of ecological stormwater management and the basic principles and techniques of LID. Ecological stormwater management involves understanding and applying ecoregion factors such as: climate, physiography/ landform, geology, soils, and plant associations. This thesis begins with a brief overview of the ecoregional factors associated with the Topeka, Kansas (KS) area. Two case studies of LID type stormwater structures are investigated. The case studies, Jackson Street and Hillcrest, are projects of the City of Topeka Water Pollution Control Division (Topeka, KS). The primary topics investigated include: background, political approval process, condition of site before implementation, general project design, stormwater design, soil, plants, LID principles and techniques used, lessons learned, and a critique of each project. Investigation methods include: personal communication with key individuals involved, and a review of site visits, drawings, specifications, and other projects documents.
Keywords: stormwater; management; low impact development; ecology; case studies; water; Landscape Architecture (0390)